Mystery shopping: study indicators in libraries - Morena de Diago, Beatriz (Revista General de Información y Documentación, 2013)
This paper revises the characteristics of the mystery shopping data collection's technique. This technique is part of methodological domain in the qualitative procedure and it´s characterized by the use of individuals trained to experience and measure any customer service process. It reviews the main codes for its regulation and the most frequent study factors in the field work for data recording. It includes a systematizing proposal of the most recurring study categories and indicators in the browsed literature for implementation of this data collection technique in any library.
Keywords: checklist; data collection techniques; mystery shopper; mystery shopping; qualitative research